“Kuygay” (“Girl’s Song”) - Nabieva Zebokhon Abdurasulovna (Zien Journals, 2022)
Yunus Rajabi, one of the learned, intelligent, selfless, philanthropic people of the 20th century, has been in the attention of the Uzbek nation for several years due to his great works. All the noble and meritorious works he performed created the ground for further development of Uzbek music. Also, the folk works of the artist are among the most valuable examples even today. One of them is the song “Kuygay” or “Girl’s Song” by the author. In this article, we discuss the history of creation and musical-theoretical analysis of this work.
Keywords: status; shashmakom; composer; hafiz